TECHNICAL PROGRESS SURVEY - BYRD STATION, ANTARCTICA. - Hoffman,C. R. (1966)
A technical survey was conducted at Byrd Station, Antarctica, in December 1965. The purpose of the survey was to obtain information on current construction problems and design adequacy in the undersnow camp. The survey showed the camp to be in generally good condition with most systems functioning well. Areas in greatest need of improvement include summer tunnel cooling, control of surface air entry and circulation, increased water production and improved maintenance on systems for surface venting of combustion gases and noxious fumes. (Author)